The Role of the Binmas Unit in Preventing Acts of Terrorism in the Jurisdiction of the Tasikmalaya Police - Hudoyo, Adel Muhammad Gabriel (Police Studies Review, 2024)
The development of terrorism in Indonesia is more on the fourth wave of terrorists. As a manifestation of Indonesia's seriousness towards terrorism, the government is obliged to prevent terrorism. Community empowerment can be carried out by the police through Binmas technical functions in conducting counseling to the community so that the community can be well educated. The purpose of this study is to describe the general picture of terrorist acts in Tasikmalaya, the role of Binmas units in conducting counseling and factors that can influence and inhibit Binmas units in carrying out efforts to prevent radicalism in Tasikmalaya Regional Police Station. This study uses a qualitative approach to the type of descriptive analysis research. The location of this research took place in the legal area of the Tasikmalaya District Police. The researcher analyzed the results of the study using management theory, communication theory, and role theory supported by the Binmas Unit concept, the counseling concept, the bhabinkamtibmas concept, and the polmas concept. Data collection techniques using interviews, document studies and observations. The validity and reliability in this study uses secondary triangulation, time, technique and sources. In analyzing data, data reduction and data presentation are performed. The results of this study reveal that by conducting counseling by the Tasikmalaya Regional Police Binmas Unit can prevent acts of terrorism in Tasikmalaya Regency. There are influencing factors, namely the lack of intensity of counseling, facilities and infrastructure of members, budget, and unsustainable approaches. From the external side there are several aspects such as the majority of the community is Muslim, lack of education levels, public awareness of the environment, but from the budget side is sufficiently met but still requires evaluation. The Binmas Unit has a role in coordinating and communicating with the community in a good manner so as to provide a good assessment of the community.